Normative data for highly educated older adults in phonemic and semantic fluency tests - Julianna Pinto de Azevedo; Katie Moraes de Almondes (Dementia & Neuropsychologia, 2023)
ABSTRACT. Verbal fluency tests are common instruments used in neuropsychological evaluation and screening for cognitive decline. Different studies have suggested normative data for these tests, but new studies that focus on different educational backgrounds are important due to the heterogeneity of the Brazilian population and the influence of educational level on verbal fluency tests. Objective: The present study aimed to provide normative data on verbal fluency tests for highly educated older adults in Brazil, as well as the influence of sex, age, and education on test performance. Methods: A total of 147 healthy volunteers (106 females and 41 males) with a mean age of 66.87 years (SD=4.52) and a minimum of 12 years of education were selected from the community and asked to perform three tests of phonemic verbal fluency (letters F, A, and S) and two tests of semantic verbal fluency (animals and fruits). Volunteers were categorized by educational level into two categories: “High School” (12 years of formal education) and “Higher Education” (over 12 years of formal education). Results: Normative data are presented in mean values and percentiles for all tests. The performance in animals, fruits, A, and S were associated with educational background. The performance in S was associated with sex. Conclusions: This study provides normative data appropriate for highly educated, healthy older adults in commonly used tests that evaluate executive functioning. The results endorse previous study findings on the influence of educational level on verbal fluency tests.